2020
DOI: 10.15252/emmm.201910812
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic lethality between VPS 4A and VPS 4B triggers an inflammatory response in colorectal cancer

Abstract: Somatic copy number alterations play a critical role in oncogenesis. Loss of chromosomal regions containing tumor suppressors can lead to collateral deletion of passenger genes. This can be exploited therapeutically if synthetic lethal partners of such passenger genes are known and represent druggable targets. Here, we report that VPS4B gene, encoding an ATPase involved in ESCRT-dependent membrane remodeling, is such a passenger gene frequently deleted in many cancer types, notably in colorectal cancer (CRC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 74 publications
4
22
0
Order By: Relevance
“…Differential expression of 57 genes was common across stages of tumorigenesis, whereas 43 and 12 genes were unique for early and advanced stages, respectively (Table S2). In addition to decreased mRNA abundance of VPS4B, which we studied previously (Szymanśka et al, 2020), we detected reduced expression of an ESCRT-I component -VPS37Bin advanced stage CRC (Fig. 1C).…”
Section: Expression Of Vps37b Is Decreased In Advanced Colorectal Cancersupporting
confidence: 70%
See 2 more Smart Citations
“…Differential expression of 57 genes was common across stages of tumorigenesis, whereas 43 and 12 genes were unique for early and advanced stages, respectively (Table S2). In addition to decreased mRNA abundance of VPS4B, which we studied previously (Szymanśka et al, 2020), we detected reduced expression of an ESCRT-I component -VPS37Bin advanced stage CRC (Fig. 1C).…”
Section: Expression Of Vps37b Is Decreased In Advanced Colorectal Cancersupporting
confidence: 70%
“…The advent of next-generation sequencing technologies has permitted unbiased screening of components orchestrating receptor transport and endolysosomal degradation in distinct pathological settings (Buser et al, 2019;Yoshida et al, 2010). Here, by mining RNA-Seq datasets we revealed differential expression of 112 endocytic machinery components across stages of CRC, several of which were previously shown to be reduced in adenocarcinoma (Kwong et al, 2005;Szymanśka et al, 2020;Tanigawa et al, 2019). In-depth validation of our in silico screen uncovered reduced mRNA and protein abundance of VPS37A and VPS37B paralogs in CRC patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although our screen suggested that VPS4A was required for VACV spread, as VPS4B was not targeted in the screen, follow-up individual depletion experiments were performed which indicated that VPS4B was rather the critical factor. These experiments revealed that, in HeLa cells, the relative abundance of VPS4A and VPS4B is markedly different, and that a complex compensatory relationship may exist between these paralogs-consistent with findings in yeast and cancer cells (Scheuring et al, 2001;Szymańska et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, these altered expression profiles also persist in the metastatic cancer cells. In contrast, Vps4-Vta1 and ALIX act as gatekeepers to terminate exocytosis and, therefore, their function is often suppressed in malignant colorectal tumors [45,46]. Most RABs show excessive expression, coordinating the production and transportation of EVs, but there are also some redundant trends (Table 1).…”
Section: Role Of Evs In Colorectal Tumorigenesismentioning
confidence: 99%